Characteristics of Hospitalized Children With a Diagnosis of Malnutrition: United States, 2010. (22nd March 2016) - Abdelhadi, Ruba A.; Bouma, Sandra; Bairdain, Sigrid; Wolff, Jodi; Legro, Amanda; Plogsted, Steve; Guenter, Peggi; Resnick, Helaine; Slaughter‐Acey, Jaime C.; Corkins, Mark R.; ,
Abstract : Introduction: Malnutrition is common in hospitalized patients in the United States. In 2010, 80, 710 of 6, 280, 710 hospitalized children <17 years old had a coded diagnosis of malnutrition (CDM). This report summarizes nationally representative, person‐level characteristics of hospitalized children with a CDM. Methods: Data are from the 2010 Healthcare Cost and Utilization Project, which contains patient‐level data on hospital inpatient stays. When weighted appropriately, estimates from the project represent all U.S. hospitalizations. The data set contains up to 25 ICD‐9‐CM diagnostic codes for each patient. Children with a CDM listed during hospitalization were identified. Results: In 2010, 1.3% of hospitalized patients <17 years had a CDM. Since the data include only those with a CDM, malnutrition's true prevalence may be underrepresented. Length of stay among children with a CDM was almost 2.5 times longer than those without a CDM. Hospital costs for children with a CDM were >3 times higher than those without a CDM. Hospitalized children with a CDM were less likely to have routine discharge and almost 3.5 times more likely to require postdischarge home care. Children with a CDM were more likely to have multiple comorbidities. Conclusions: Hospitalized children with a CDM are associated with more comorbidities, longer hospital stay, and higher healthcare costs than those without this diagnosis. These undernourished children may utilize more healthcare resources in the hospital and community. Clinicians and policymakers should factor this into healthcare resource utilization planning. Recognizing and accurately coding malnutrition in hospitalized children may reveal the true prevalence of malnutrition.